Capacity for glaucoma screening and treatment at primary and secondary level health centers in Uganda: Situational analysis - Onyango J; Kwaga T; Namwase S; Tusingwire P; Arunga VN; Atwine D; Arunga S (Journal of Ophthalmology of Eastern, Central and Southern Africa (JOECSA), 2024)
Objective: To measure the capacity for glaucoma screening and treatment at primary and secondary level health centers in southwestern Uganda. Methods: In a cross-sectional study, we used quantitative methods to conduct a situation analysis at primary (health center IVs, district hospitals) and secondary level health facilities (referral hospitals) within southwestern Uganda. Survey questionnaires were administered to eye health workers at the health facilities to ascertain glaucoma awareness. An inventory checklist was used to establish equipment and consumables available to screen, diagnose and treat glaucoma in the primary and secondary level setting. Results: There were 86 primary and secondary level health facilities enrolled in this study. Out of the 86 facilities, 45 (52.3%) did not have any eye care worker. Majority lacked functioning basic eye equipment and consumables for the diagnosis of glaucoma. Only 28 (32.6%) facilities had a direct Ophthalmoscope. Timolol was the most common eye drop and was available in 12 (14%) of the health facilities. The lowest level of knowledge about glaucoma was observed at health center IVs (34.6%), while the highest level of knowledge was observed at regional referral hospitals (82.7%). Conclusion: There is need to improve the availability of equipment, diagnostic consumables and essential medicines for glaucoma at health facilities in southwestern Uganda. Additionally, training and deployment of more eye care workers at the primary and secondary health facilities is necessary for quality access to eye care services.
Keywords: Glaucoma; Screening; Developing; Uganda; Sub-Saharan Africa